Proceedings of Accretion Processes in Cosmic Sources — PoS(APCS2016) 2018
DOI: 10.22323/1.288.0052
|View full text |Cite
|
Sign up to set email alerts
|

Galactic and extragalactic novae - A Review

Abstract: The outbursts of classical novae are among the strongest explosions in the Universe. The multifrequency observations are contributing to understanding the process of explosions and of the long term evolution. In this review, I discuss the observations of novae over the electromagnetic spectrum, focusing on the morphology of the decline light curves, the spectroscopic investigations, the long term evolution, the recurrent novae, the gamma ray emission in novae, extragalactic novae and the gravitational emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Classical novae are the result of a thermonuclear runaway on the surface of a white dwarf which is accreting mass from a less evolved companion through Roche-lobe overflow. A review can be found in Poggiani [11] or, for a more extensive description, the reader is referred to Bode & Evans [2] Although novae can be as bright as naked eye objects, they can be very faint when the thermonuclear burning on the white dwarf is finished. For novae discovered in the last two decades the accuracy of their position is already estimated within a few arcseconds while the nova is still at maximum light.…”
Section: Introductionmentioning
confidence: 99%
“…Classical novae are the result of a thermonuclear runaway on the surface of a white dwarf which is accreting mass from a less evolved companion through Roche-lobe overflow. A review can be found in Poggiani [11] or, for a more extensive description, the reader is referred to Bode & Evans [2] Although novae can be as bright as naked eye objects, they can be very faint when the thermonuclear burning on the white dwarf is finished. For novae discovered in the last two decades the accuracy of their position is already estimated within a few arcseconds while the nova is still at maximum light.…”
Section: Introductionmentioning
confidence: 99%